Open Access Medical Journals: Promise, Perils, and Pitfalls. (May 2019) - Baker, Eileen F.; Iserson, Kenneth V.; Aswegan, Andrew L.; Larkin, Gregory L.; Derse, Arthur R.; Kraus, Chadd K.
Abstract : The number of both print and electronic open access (OA) journals has increased dramatically. Although electronic availability of information on the Internet may offer greater potential for information sharing, it also gives rise to "predatory" journals and deceptive publishers. In this Invited Commentary, the authors describe both the opportunities and potential perils that come with OA publications. Definitions for four models of legitimate OA are provided: the gold model, the green model, the platinum model, and the hybrid model. Benefits and risks of each model are discussed. The authors also distinguish between legitimate OA journals and predatory journals, highlighting several existing tools and resources for distinguishing between the two. Finally, the authors provide a checklist to help authors evaluate the policies and processes of journals and thereby avoid predatory publications.